Point-of-Care Diagnostic Testing for Emerging and Existing Poultry Viral Respiratory Pathogens Using Loop-Mediated Isothermal Amplification - Ben Enyetornye; Aurelle Yondo; Binu T. Velayudhan (Pathogens, 2025)
Accurate, rapid and inexpensive diagnosis of poultry respiratory pathogens remains a challenge, especially in many developing countries. Meanwhile, poultry respiratory pathogens are a major threat to poultry production worldwide, accounting for billions of dollars in economic loss to the sector. Early and accurate diagnosis of these diseases is critical for economic poultry production. Molecular diagnostic methods, including PCR-based techniques, have been developed and used to fill this gap, but unfortunately, these techniques require skilled technicians, relatively costly equipment and reagents and can only be performed in a laboratory setting. This warrants the development of other diagnostic tools, which can be used in the field even by unskilled personnel. In this review, we discussed the genesis, challenges, advances and prospects of loop-mediated isothermal amplification (LAMP) for the detection of poultry respiratory pathogens at the flock side, especially in resource-constrained countries. We highlighted the application of LAMP in routine poultry disease surveillance and early outbreak detection, underscoring its value as a transformative diagnostic tool in poultry production. The development and use of a point-of-care (POC) LAMP assay that can be used to screen for these poultry respiratory pathogens simultaneously enhance disease surveillance and diagnosis.